Exploring the Length and Complexity of Couples Travel Decision Making. (November 2017) - Smith, Wayne W.; Pitts, Robert E.; Litvin, Steve W.; Agrawal, Deepti
A quasi-experiment is used to examine the dynamics of the shared decision-making process by observing couples in real time as they make decisions about an overnight stay at a luxury resort. Observations and video recordings of the decision processes of 24 couples were coded and analyzed. The time to final decision, number, and type of tactics used were found to vary with couples' length of experience with one another. Observation indicated that couples with greater travel experience together relied on "predealing" based on their experience together to avoid conflict, while less-experienced couples' decisions were more likely to yield winners and losers. These findings and those related to the use of persuasive tactics by members of the couple dyads provide the basis for specific recommendations for marketing travel products.